KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS PROSTATE CANCER SCREENING AMONG MEN AGED 40-60 YEARS ATTENDING KISENYI HEALTH CENTRE IV, KAMPALA. A CROSS-SECTIONAL STUDY. - KAMWESIGE , JOSHUA; Otieno, Joash Odiwuor (Student's Journal of Health Research Africa, 2024)
Background: Purpose of the study: The purpose of the study was to determine the knowledge, attitudes, and practices toward prostate cancer screening among men aged 40-60 years attending Kisenyi Health Centre IV, in Kampala. Objectives: The objectives of the study were to determine the knowledge, attitudes, and practices towards prostate cancer screening among men aged 40-60 years attending Kisenyi Health Centre IV, Kampala, whereas the specific objectives were to, determine the knowledge, assess the attitudes, and determine the practices of men aged 40-60 years towards prostate cancer screening. Methodology: The study employed a descriptive cross-sectional study design. it facilitated the collection of adequate data despite the limited time frame that was allocated as well as the limited resources that were available for the study. Results: Study findings revealed that the majority 90% were urban residents and 10% were rural residents,72 (62%) respondents were between (40-49) years and 44(38%) were between (50-60) years,111(96%) respondents were married and 5(4%) were divorced. 114(98%) had good knowledge, 106(91%) had positive attitudes and 95(82%) had never been screened for prostate cancer. Conclusion: From the findings majority of the respondents had sufficient knowledge about prostate cancer and positive attitudes toward prostate cancer screening practices however screening practices were still very poor. Recommendations: With support, and funding from the Government of Uganda and the non-government organizations through the Ministry of Health, I recommend that more prostate cancer screening departments be established on a health Centre level, services provided should be free of charge, prostate cancer screening messages should be broadcasted in all languages to the public.